TAHAPAN-TAHAPAN DALAM MANAJEMEN KURIKULUM PADA LEMBAGA PENDIDIKAN ISLAM - Arfandi Arfandi; Munif Shaleh (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The preparation and development of the curriculum can not be done recklessly. In Islam, education has the characteristics different from education in general, for example Islamic education emphasizes akhlak, combines science and charity, and so forth. T management science approach is required in the preparation or development of the curriculum, so that the Islamic education curriculum development reflects the characteristics of the school. There are three stages in curriculum development: curriculum planning, curriculum implementation, and curriculum evaluation. This paper contains an explanation of these three stages in relation to the principles, fundamentals and approaches in curriculum development. The concept of management is integrated with the concept of curriculum development in an integral way, so the two concepts become a single concept of curriculum management in Islamic education.